Measuring rural women empowerment through participation in women Self Help Groups in Nigeria – an empirical analysis - Abu Samah, Asnarulkhadi; Hamsan, Hanina Halimatusaadiah; Ndaeji, Muhammad Ndas (Marsland Press, 2013)
In recent year, women’s empowerment through participation is said to be at the center stage in global development. The paper seeks to examine the benefits of participation in Self Help Group’s (SHG) activities among rural women in Nigeria. Women empowerment through participation in SHG which is the focus of this paper is a process in which women are able to organize themselves to increase self-reliance and to assert their independent right to make choices in order to effectively promote their well being. The extent to which rural women are empowered through participating in SHG is the essence of the paper. A sample of 282 SHG members were selected through simple random (lottery method) out of 30 SHGs identified in agricultural activities from the three senatorial districts of Niger State and a schedule was designed and administered among the respondents. The study revealed that even though women approach is newly introduced in the study area (Niger State), the majority of women who constituted as respondents of this study have benefited considerably as most of them have been earning certain income thereby supplementing their family income. The study also proved that a large number of respondents have emphasized positive changes in their well being. The paper concludes that SHG approach is an instrument for rural women empowerment and poverty reduction in Nigeria. Nigerian rural women need to extend their participation in group’s approach as the strategy has become a valuable way for women sustainable development.